2020
DOI: 10.1186/s12933-020-01051-2
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for heart failure incidence according to the transition in metabolic health and obesity status: a nationwide population-based study

Abstract: Background: We aimed to investigate the hazard of hospitalization for heart failure (hHF) according to the transitions in metabolic health and obesity status. Methods: The Korean National Health Insurance Service datasets from 2002 to 2017 were used for this nationwide, longitudinal, population-based study. The hazard of hHF was analyzed according to the eight groups stratified by stability in metabolic health and transition in obesity status among initially metabolically healthy adults who underwent two cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 57 publications
(73 reference statements)
1
36
1
Order By: Relevance
“…When compared to stable MHNO individuals, subjects who retained MHO during a mean follow-up of 3.70 years, had a 17.3% increased hazard of hospitalization for heart failure (hHF). Furthermore, individuals who shifted from MHO to MHNO had a 34.3% lower hazard of hHF [33]. This is in agreement with previous observations showing that subjects with MHO may have no or only a moderately increased risk of myocardial infarction, but are not protected from heart failure [34], which is also strongly driven by obesity [35,36].…”
Section: Metabolic Health As a Transient Statesupporting
confidence: 91%
See 2 more Smart Citations
“…When compared to stable MHNO individuals, subjects who retained MHO during a mean follow-up of 3.70 years, had a 17.3% increased hazard of hospitalization for heart failure (hHF). Furthermore, individuals who shifted from MHO to MHNO had a 34.3% lower hazard of hHF [33]. This is in agreement with previous observations showing that subjects with MHO may have no or only a moderately increased risk of myocardial infarction, but are not protected from heart failure [34], which is also strongly driven by obesity [35,36].…”
Section: Metabolic Health As a Transient Statesupporting
confidence: 91%
“…While subjects with transient MHO had an increased risk (152%) of a composite subclinical atherosclerosis endpoint, the risk was statistically not different (8%) in subjects with stable MHO, when compared to subjects who were metabolically healthy and non-obese (MHNO) [32]. Of interest, persistent MH in obesity does not protect from heart failure as was most recently shown in an analysis of data from the Korean NHIS datasets from 2002 to 2017 [33]. When compared to stable MHNO individuals, subjects who retained MHO during a mean follow-up of 3.70 years, had a 17.3% increased hazard of hospitalization for heart failure (hHF).…”
Section: Metabolic Health As a Transient Statementioning
confidence: 87%
See 1 more Smart Citation
“…One previous study followed patients with metabolic syndrome for 6 years and revealed that they were at 2.3, 2.6, and 2.1 (normal weight, overweight, and obese, respectively) times higher risk of developing HF than those without metabolic syndrome (34). Another recent longitudinal study revealed that the hospitalization for HF was increased in obese subjects who transitioned from metabolically healthy to unhealthy status (37). Among individuals without metabolic syndrome, obese individuals were at a higher risk of hospitalization for HF than non-obese individuals (37).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent longitudinal study revealed that the hospitalization for HF was increased in obese subjects who transitioned from metabolically healthy to unhealthy status (37). Among individuals without metabolic syndrome, obese individuals were at a higher risk of hospitalization for HF than non-obese individuals (37). The two previous studies classified patients according to their metabolic syndrome, which indicates meeting three or more of the five criteria, including waist circumference, BP, fasting TG level, fasting HDL-C, and FPG levels (38).…”
Section: Discussionmentioning
confidence: 99%